Safety monitoring of chloroquine and hydroxychloroquine in COVID-19 patients in Indonesia on QT prolongation: hospital based monitoring study - Anggoro Budi Hartopo; Jarir At Thobari; Togi Junice Hutadjulu; Tri Asti Isnariani; Umi Sa'adatun Nikmah; Lukman Ade Chandra; Pompini Agustina Sitompul; Rizki Amalia Gumilang; Luhur Pribadi; Deva Bachtiar; Anwar Santoso (Indonesian Journal of Pharmacology and Therapy, 2023)
Chloroquine (CQ) and Hydroxychloroquine (HCQ) are the challenging drugs used for COVID-19. Several studies show its beneficial, however, both medications can prolong the QTc interval and increase the risk of patients for torsades de pointes and death. The Tisdale score is identified to have successfully predicted the at-risk population of side effects of these drugs. This study aim to evaluate the QT prolongation caused by the administration of chloroquine and hydroxychloroquine in COVID-19 patients and the association with the treatment outcomes based on their Tisdale score. We conducted an observational study on 213 hospitalized patients with confirmed or suspect COVID-19 in 6 referral hospitals in Indonesia. All baseline demographic such as age and gender, RT-PCR test result, severity of disease, history of cardiovascular disease (myocardial infarction, heart failure, hypertension), serum kalium level at baseline, and the use of medication associated with risk QTc interval prolongation were collected. The Tisdale risk score was used for predicting high-risk patients for QT corrected (QTc) interval prolongation. Out of 213 patients who were treated with CQ/HCQ, there were 60 (28.2%) patients had QTc interval prolongation, included 43 patients (20.2%) who had normal QTc interval at baseline and at the end of treatment had prolong interval; or 17 patients (8.0%) who had QTc interval more than 470 msec at baseline and QTc interval prolongation was worsen at the end of treatment. Several factors, including age more than 50 years, COVID-19 confirm PCR, and had comorbidity heart failure, were statistically significant associated with QTc interval prolongation. The high-risk score of Tisdale score have increased risk significantly on QTc interval prolongation (RR: 2.15, 95%CI 1.07-4.32) and associated with risk of death (RR: 3.50, 95%CI 1.34-9.13) compared to low-risk score. Our findings showed that the treatment of CQ/HCQ in COVID-19 patients is associated with QTc prolongation. The Tisdale score can be used as a valuable tool to predict the COVID-19 patients’ outcome after treatment of these QTc-prolonging drugs.